Preliminary assessment of genotoxic effects induced by radiation from EAST using Vicia faba micronucleus assay. (1st June 2021) - Zhang, Hong; Hu, Liqun; Zhong, Guoqiang; Huo, Zhipeng; Chen, Yuqing; Zhao, Sheng; Huang, Liangsheng
Abstract: During long-pulse deuterium plasma operations in the Experimental Advanced Superconducting Tokamak (EAST), a mixed radiation field is generated, which is mainly composed of fusion neutrons, gamma rays, and x-rays. More accurate and effective dose monitoring methods have been developed and established to determine the ionizing radiation intensity both for the stable operation of the device and for the radiation safety of personnel. As far as we know, there are few reports about the biological effects of radiation induced by fusion neutrons and γ radiation, which are of vital importance for the assessment of radiation hazards presented by fusion devices, such as EAST, to human beings and the environment. In this study, three positions in the EAST hall were selected to detect genotoxic effects induced by nuclear fusion radiation using a Vicia faba micronucleus (MN) test for the first time. The doses of neutrons and gamma rays at these places were measured by thermoluminescence dosimeters four times between June 2019 and May 2020. The radiation doses decreased as the distances from the EAST device shell gradually increased from S1 to S3. The radiation in the EAST hall resulted in a significant induction of MN in the Vicia faba root tip cells compared to a negative control, which was different from the MN frequency induced by fission neutrons, γ -rays and other kinds of radiation in previous studies. These results indicate the existence of potential genotoxic effects induced by radiation from EAST which is different from other radiation and suggest that personnel should not be permitted to enter the experimental hall during the discharge process, and that radiation protection measures should be taken during necessary maintenance to avoid radiation damage. These newly acquired results will certainly increase our knowledge about the biological effects induced by radiation from nuclear fusion and provide good data support for developing more effective environmental and personnel fusion radiation protection.